Evaluation of psychological morbidities like depression, anxiety and stress as risk predictors of periodontitis using a risk assessment model: an analytical cross-sectional study - Mukherjee, Souma Shankar; Srivastava, B. K.; Roy, Sanatanu Sen; Manchanda, Kavita; Mukherji, Ishan; Chavan, Khechari; Debnath, Arpan (International Journal Of Community Medicine And Public Health, 2025)
Background: Sedentary lifestyles along with the impact of COVID-19 has increased negative life experience events like depression, anxiety and stress among people. This often increases the liability towards periodontal disease. Methods: An analytical cross-sectional study was conducted on a sample of 340 individuals, from July 2022 to December 2022, visiting the outpatient department of KLE College of Dental Sciences, Bengaluru. Demographic details of those subjects were obtained through a questionnaire. Depression, anxiety and stress were calculated using the DASS 21 scale and the participants were divided into two groups based on the DASS score. Periodontal risk assessment was done using the Lang and Tonetti model. Association between psychological morbidities and periodontal risk was done using chi-square test and logistic regression analysis. Results: Out of the 340 participants, 42.9% of the females, 71.7% of the participants with BMI≥25, 15.8% of the diabetics, 11.1% of the hypertensives and 75.2% of the current smokers were suffering from some form of psychological morbidity. Furthermore, binary logistic regression analysis suggested that covariates like gender, education and risk of periodontitis were significantly associated with psychological morbidity. Conclusions: The present study suggested that increase or decrease in the risk of periodontitis was significantly associated with the increase or decrease in the level of psychological morbidity.